Association of bisphenol A exposure with dietary quality indices in Spanish schoolchildren. (August 2016) - Rivas, Ana; Monteagudo, Celia; Heras-Gonzalez, Leticia; Mariscal-Arcas, Miguel; Lorenzo-Tovar, Maria Luisa; Olea-Serrano, Fátima
Abstract: Young children, whose growth and development are highly dependent on the endocrine system, are particularly vulnerable to endocrine disruptor exposure. The main objectives of this study were to measure BPA migration levels from cans, fruit juice bottles/packs, and microwave containers used for food/drinks consumed by a sample of 6- to 8-year old schoolchildren in Spain and to estimate the relationship between their resulting BPA exposure and diet quality index scores (Mediterranean Diet Score and Breakfast Quality Index). The mean BPA concentration was 11.8 ng/mL for vegetable cans, 22.1 ng/mL for pulse cans, 3.6 ng/mL for juice bottles/packs, and 1.2 ng/mL for microwave containers. Results revealed a significant association between the Mediterranean Diet Score and low BPA exposure of the children. BPA exposure below the median level was significantly associated with a higher score in both the first-grade (P = 0.030) and second-grade (p = 0.0001) groups. However, no association was found between BPA exposure and the Breakfast Quality Index. In conclusion, children with a stronger adherence to a Mediterranean-like diet appear to be less exposed to BPA migrating from food packaging and microwave containers. Further research is warranted on the inadvertent exposure of children to endocrinedisrupting chemicals from these sources. Graphical abstract: Highlights: BPA migration was measured from various types of containers of food consumed by children. The relationship between children's BPA exposure and diet quality scores was evaluated. Children with stronger adherence to a Mediterranean diet are less exposed to BPA.